First experience of endovascular balloon occlusion of the aorta in the wounded with hemorrhagic shock during the war in Ukraine - K.V. Gumeniuk; Yu.Yu. Sivash; V.M. Rogovskyi; D.M. Beshley; А.Т. Slobodianiuk (Медицина неотложных состояний)
Background. Resuscitative endovascular balloon occlusion of the aorta (REBOA) is used worldwide to stop bleeding in trauma and wounds in patients with hemorrhagic shock. REBOA allows for the hemodynamic stabilization, patient transportation and final bleeding control. The study aims to demonstrate the capabilities of REBOA as a method of bleeding control in the wounded with hemorrhagic shock in the context of war in Ukraine. Materials and methods. Five AFU servicemen who sustained mine-blast wounds in the Eastern Ukraine as a result of shelling by Russian troops were delivered with signs of internal bleeding and hemorrhagic shock to the primary and secondary levels of medical care (Role 1, 2). The REBOA balloon catheter was inserted and inflated by surgeons working in stabilization centers or advanced surgical teams. Upon admission, all patients underwent chest and abdominal ultrasound according to the FAST protocol. We used COBRA-OS 4 Fr and ER-REBOA 7 Fr balloon catheters. The positioning of the balloon in the aorta was performed according to external anatomical landmarks (3 cases) and ultrasound (2 cases). In all clinical cases, the balloon catheter was placed in zone I. In one case, the balloon was moved from zone I to zone III (control of the source of bleeding). The duration of aortic occlusion ranged from 15 to 50 minutes. Immediately after removal of the introducer, manual compression of the puncture site was used (3 cases) or suturing of the arteriotomy (2 cases). Results. The sources of bleeding in our clinical cases were injuries of the iliac vessels (2 cases), the renal artery (1 case), and injuries of the inferior vena cava and liver (2 cases). Four patients were evacuated to a higher level of medical care after the REBOA was installed. In one case, there were complications from vascular access (femoral artery thrombosis). We were unable to save one wounded soldier, most likely due to the delay in evacuation from the previous stage, the severity of injury, and massive blood loss. Conclusions. As our observations have shown, the use of REBOA in combat conditions allows not only to stabilize hemodynamics in the wounded with severe combined trauma and bleeding but also to conduct a successful evacuation to a higher level of medical care to stop bleeding ultimately. REBOA can be successfully used at the prehospital stage. This requires clearly defined indications for the technique’s use, training of medical personnel, and provision of balloon catheters to medical units of the Armed Forces of Ukraine.